2020
DOI: 10.1002/adma.201908120
|View full text |Cite
|
Sign up to set email alerts
|

Organic Electrochemical Transistors Based on the Conjugated Polyelectrolyte PCPDTBT‐SO3K (CPE‐K)

Abstract: PCPDTBT-SO3K (CPE-K), a conjugated polyelectrolyte, is presented as a mixed conductor material which can be used to fabricate high transconductance accumulation mode organic electrochemical transistors (OECTs). OECTs have been utilized in a wide range of applications such as analyte This article is protected by copyright. All rights reserved. 2 detection, neural interfacing, impedance sensing and neuromorphic computing. We demonstrate the use of interdigitated contacts to enable high transconductance in a rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 65 publications
2
49
0
Order By: Relevance
“…[ 32,35,37,40–42 ] Furthermore, copolymerizing conjugated polymers with electrolyte polymers also increases ionic conductivity while preserving some electronic mobility. [ 43,44 ] Including additives/plasticizers such as ethylene glycol or ionic liquids into the active layer (e.g., poly(3,4‐ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS)) also enhances transconductance via improved morphologies while maintaining comparable ion uptake. [ 45–49 ]…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…[ 32,35,37,40–42 ] Furthermore, copolymerizing conjugated polymers with electrolyte polymers also increases ionic conductivity while preserving some electronic mobility. [ 43,44 ] Including additives/plasticizers such as ethylene glycol or ionic liquids into the active layer (e.g., poly(3,4‐ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS)) also enhances transconductance via improved morphologies while maintaining comparable ion uptake. [ 45–49 ]…”
Section: Figurementioning
confidence: 99%
“…[32,35,37,[40][41][42] Furthermore, co polymerizing conjugated polymers with electrolyte polymers also increases ionic conductivity while preserving some electronic mobility. [43,44] Including additives/plasticizers such as ethylene glycol or ionic liquids into the active layer (e.g., poly (3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS)) also enhances transconductance via improved morphologies while maintaining comparable ion uptake. [45][46][47][48][49] The interfacial area between the electrolyte (typically liquid) and the active layer (solid) is a critical OECT component since it directly affects ion exchange between the two phases.…”
mentioning
confidence: 99%
“…Other than the above‐mentioned classes of MIECs based on polythiophenes, there are only a very few reports of OECTs using the second‐generation conjugated polymers, based on donor–acceptor structures as p‐type MICEs. [ 20,21 ] Donor–acceptor copolymers, especially those incorporating diketopyrrolopyrrole (DPP) moieties as acceptor units can exhibit high charge carrier mobilities and their synthetic strategies to tune the chemical structures over a wide range are well established. [ 22,23 ] We as well as others have earlier shown that the flanking units, solubilizing side‐chains and comonomers can be adjusted deliberately to attain the desired type of charge transport and alignment.…”
Section: Introductionmentioning
confidence: 99%
“…Organic electrochemical transistors (OECTs) have attracted extensive attention recently due to their capability of transducing ionic signals into electronic ones at low electrochemical potentials (<1 V), which have greatly facilitated the advance of low‐voltage electronics, [1–5] including bioelectronics, [6–9] printed logic circuits, [10–12] and memory/neuromorphic devices [13–16] . Up to now, p‐type (hole‐transporting) polymer semiconductors have been intensively investigated as the channel materials in OECTs with the product ( μC *) of charge carrier mobility ( μ) and volumetric capacitance ( C *), the key Figure of merit determining the performance of OECTs, up to 522 F cm −1 V −1 s −1 achieved [17–21] . However, the development of n‐type (electron‐transporting) polymers lags greatly behind with the μC * values typically in the range of only 0.1–1 F cm −1 V −1 s −1 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%